Evaluating the productivity of selected in vitro culture techniques for the production of a locally isolated entomopathogenic nematode - Matlhabe, Ofentse (My University, 2018)
Entomopathogenic nematodes (EPNs) of the genera Steinernema and Heterorhabditis have gained interest as biocontrol agents of insect pests due to their ability to search and kill soil dwelling insects. Some members of the Oscheius genus have been shown to have insecticidal abilities as a result of their association with bacteria in the Serratia genus. This has led to the consideration of the Oscheius as an EPN genus. The biocontrol potential serves as an incentive for studying EPNs and various production methods for their commercial use as biopesticides. A putative EPN was isolated from soil samples collected at Brits in the North West Province of South Africa. 18S rDNA based identification indicated that it belonged to the Heterorhabditis genus however, phylogenetic analysis and symptoms on Galleria mellonella larvae suggested that the nematode may belong to the Oscheius genus. The bacterial symbiont associated with this nematode was found to be a strain of Serratia marcescens, through 16S rDNA based sequencing and phylogenetic analysis. Various in vitro production methods were evaluated for their effect in the production of Oscheius L8 MCB. These include monoxenic and axenic culturing, growth media supplementation, and production in solid and liquid state. Axenic cultures were found to produce high maximum yields of EPNs (78 600 EPNs/ml) compared to monoxenic cultures (53 833 EPNs/ml). It was concluded that axenic culturing was efficient for the production of this species. Oscheius L8 MCB was cultured in NB supplemented with varying concentrations of oil and glucose. Supplementation of NB with 2% canola produced a significant amount of EPNs in reduced culture times, but NB supplemented with 4% canola oil and 25mg/ml glucose increased nematode yield but prolonged the culture time. It is noted that media composition (with regards lipid and carbohydrate content) plays an important role in nematode yield and culture time and thus optimization of these components is critical for efficient nematode production. Solid state and liquid state production of Oscheius L8 MCB showed that solid state cultures allowed for early IJ production, whereas liquid state culturing produced the highest IJ yield (36 000 IJs/ml). The reduced culture period, makes solid state production more cost effective and preferable for mass production. However, liquid production can still be used as it offers the benefits of high nematode yeild and efficient recovery of nematodes from culture. The in vitro methods of EPN production have been reported to have an effect on the efficacy of the EPNs against insect hosts. Dose-response assays showed that in vivo produced EPNs resulted in high G. mellonella larvae mortality at lower concentrations compared to solid and liquid in vitro methods. Larvae infected with in vivo produced Oscheius L8 MCB produced a high number of emerging IJs compared to larvae infected with EPNs produced using axenic in vitro culturing methods. The differences between mortality and IJ emergence in larvae infected with solid state and liquid state cultured EPNs were marginal. Therefore, it is concluded that axenic culturing methods may reduce the efficacy of Oscheius L8 MCB against insect hosts.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science, Johannesburg, May 2018.
Keywords: Nematodes; Bioreactors; Bacteria